Intravenous Thrombolysis May Not Improve Clinical Outcome of Acute Ischemic Stroke Patients Without a Baseline Vessel Occlusion - Tian, Huiqiao; Parsons, Mark W.; Levi, Christopher R.; Cheng, Xin; Aviv, Richard I.; Spratt, Neil J.; Kleinig, Timothy J.; O'Brien, Billy; Butcher, Kenneth S.; Lin, Longting; Zhang, Jingfen; Dong, Qiang; et al. (Frontiers in Neurology, 2018)
Background and Purpose: The benefit of thrombolysis in ischemic stroke patients without a visible vessel occlusion still requires investigation. This study tested the hypothesis that non-lacunar stroke patients with no visible vessel occlusion on baseline imaging would have a favorable outcome regardless of treatment with alteplase. Methods: We utilized a prospectively collected registry of ischemic stroke patients (the International Stroke Perfusion Imaging Registry (INSPIRE) who had baseline computed tomographic perfusion and computed tomographic angiography. The rates of patients achieving modified Rankin Scale (mRS) 0-1 were compared between alteplase treated and untreated patients using logistic regression to generate odds ratios. Results: Of 1569 patients in the INSPIRE registry, 1277 were eligible for inclusion. Of these, 306 (24%) had no identifiable occlusion and were eligible for alteplase, with 141 (46%) of these patients receiving thrombolysis. The treated and untreated groups had significantly different median baseline National Institutes of Health Stroke Scale (alteplase 8, interquartile range (IQR) 5-10, untreated 6, IQR 4-8, P<0.001) and median volume of baseline perfusion lesion (alteplase 5.6 mL, IQR 1.3-17.7 mL, untreated 2.6 mL, IQR 0-6.7 mL, P<0.001). After propensity analysis, alteplase treated patients without a vessel occlusion were less likely to have an excellent outcome (mRS 0-1; 56%) than untreated (78.8%, OR, 0.42, 95% confidence interval, 0.24-0.75, P=0.003). Conclusions: In this non-randomized comparison, alteplase treatment in patients without an identifiable vessel occlusion did not result in higher rates of favorable outcome compared to untreated. However, treated patients displayed less favorable baseline prognostic factors than the untreated group. Further studies may be required to confirm this data.